Optimalisasi Modal Sosial Masyarakat Jatiwangi Art Factory Sebagai Strategi Transformasi Keberlanjutan Sosial (Studi Kasus Di Desa Jatisura Kabupaten Majalengka) - Dini Miftakhul Jannah; Sardin; Siti Nurbayani (UNIB Press, 2025)
Social capital is a key factor in facilitating sustainable social transformation which mechanisms rely on the function of social networks, trust, and shared social norms. In Jatiwangi, Majalengka Regency of West Java, an interesting case emerged which shows how social capital can be a driver of sustainable social transformation. This research aims to analyse the social capital of the Jatiwangi Art Factory Community (JAF) as a strategy for sustainable social transformation. This research uses a qualitative approach with a case study method and theoretical utalizes framework proposed by Pierre Bourdieu's Social Capital and Arnold Toynbee's Theory of Social Change. Research findings show that JAF has succeeded in optimizing social capital as the main tool in creating sustainable social transformation that occurred was the result of a process of social interaction, capital accumulation and creative responses to social and economic challenges, there were present of shared values ​​of mutual cooperation, creativity and cultural expressions that were part of the community's mindset and actions. JAF has also changed people's habits that were previously oriented towards the roof tile industry into a community that uses art as a means of artistic expression and sustainable economic livelihood.